Understanding evidence-informed decision-making: a rural interorganizational breastfeeding network - Sionnach Lukeman; Barbara Davies; Charmaine McPherson; Josephine Etowa (BMC, 2019)
Abstract Background Networks are a vehicle for mobilizing knowledge, but there is little research about evidence-informed decision-making in community settings. Breastfeeding is a powerful intervention for population health; combined system and community interventions can increase exclusive breastfeeding rates by 2.5 times. This study examined evidence-informed decision-making within an interorganizational network, including the facilitators and barriers to achieving network goals. Methods A mixed method case study design was used. The primary sources of data were focus group discussion and questionnaire administration. Data were analyzed concurrently using framework analysis and social network analysis. Results Key findings were at the interorganizational and external levels: 1) Relationships and trust are connected to knowledge exchange 2) Need for multiple levels of leadership. Conclusions The findings of this study have potential implications for enhancing the use of evidence-informed decision-making as other networks work toward Baby Friendly Initiative (BFI) designation and also highlights the potential for network maps to be used as a knowledge mobilization tool.